2008
DOI: 10.1063/1.2993217
|View full text |Cite
|
Sign up to set email alerts
|

Determination of helicities in unidirectional assemblies of graphitic or graphiticlike tubular structures

Abstract: Here we propose a universal method for the determination of all helicities present in unidirectional assemblies of hexagon-based graphitic or graphiticlike tubular structures, e.g., multiwalled or bundled carbon nanotubes (CNTs) or boron-nitride nanotubes and their structural analogs. A critical dimension characteristic of a fundamental structural property, i.e., the atomic bond length, is discerned from electron diffraction patterns by which all helicities present in the assemblies are identified. Using this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Nanotube EBD measurements have made a big leap forward since then [16], and these early pictures can now be interpreted as bundles with a range of chiral angles close to armchair structures. This generally agrees with recent EBD measurements on PLV nanotubes that show broad chiral angle distributions skewed towards armchair structures [17].…”
supporting
confidence: 81%
“…Nanotube EBD measurements have made a big leap forward since then [16], and these early pictures can now be interpreted as bundles with a range of chiral angles close to armchair structures. This generally agrees with recent EBD measurements on PLV nanotubes that show broad chiral angle distributions skewed towards armchair structures [17].…”
supporting
confidence: 81%
“…The chiral indices, ( n , m ), of all the three shells at any cross section in the TWNT could be determined accurately (see the Supportin Information, Fig. S7–S9) 22, 23. The results show that this TWNT maintains a constant chiral index for each shell through the length of 25 to 60 mm (electron diffraction patterns of these two positions were shown in Fig.…”
Section: Chiral Indices Diameters and Chiral Angles Of Eight Twnts Wmentioning
confidence: 82%
“…A-priori this grouping is unknown. However, Jiang et al showed that d2 and d3 belonging to the same layer of a MWNT should form a conjugated pair [48] with the following property: the bigger d3, the less is d2, and vice versa. Based on this principle, Deniz et al proposed a zone method for the accurate grouping of layer-lines [49].…”
Section: Measuring Axial Positions Of Layer-linesmentioning
confidence: 99%